MPK Krakow quality services ? assessment of the qualitative components that are most important from the passenger?s point of view - Brożyna, Ewa (AUTOBUSY – Technika, Eksploatacja, Systemy Transportowe, 2018)
This article raises a subject of quality of transport services in public transport. The author presented in it the results of her research conducted among passengers of Miejskie Przedsiębiorstwo Komunikacyjne S.A. in Kraków, which showed that the level of passengers? satisfaction of the quality of this communication is almost good (the average score was 3.61 in the five-point scale of assessments). The research allowed to acquire knowledge about the perception of the quality of MPK Kraków services by passengers and provided practical tips and suggestions regarding the directions of actions that can be taken to improve the quality of transport services at MPK Kraków. The research has been divided into two parts. Part of the research discussed in this article concerns aspects of quality most important from the point of view of the average passenger: frequency of running, punctuality of running, convenience, cost of travel and safety.